Outcomes of transecting urethroplasty in management of different types of bulbar urethral strictures: single center experience - Atwa, Ayman Moussa; Hassan, Ayman Ahmed; Orabi, Samir Shabaan; Elgamal, Samir Abdelhakim; Elgamal, Osama Mostafa (International Surgery Journal, 2021)
Background: The study aimed to evaluate the outcomes of transecting bulbar urethroplasty techniques used for management of bulbar urethral stricture as regards the success rate and sexual dysfunction. Methods: Our study was a prospective study and it was carried out at urology department Tanta university, Egypt. The study was approved our ethical committee and an informed consent was obtained from all participants. Thirty patients underwent transecting urethroplasty either excision and primary anastomosis (EPA) or augmented anastomotic urethroplasty. Assessment of the sexual function by sexual health inventory for men (SHIM) questionnaire and postoperatively. Retrograde urethrogram (RGU) and micturating cystourethrogram (MCUG) were performed by an experienced urological surgeon. Results: The age of studied patients ranged from 15-72 years with a mean of 41±13.87. The length of stricture ranged from 2-3 cm with a mean of 2.57±0.38. The stricture was non obliterative in 13 patients (43.3%), obliterative in 4 patients (13.3%) and near obliterative in 13 patients (43.3%). Anastomotic urethroplasty was carried out in 20 out of 30 patients (66.7%) and augmented anastomotic urethroplasty was carried out in 10 out of 30 patients (33.3%). The success rate was 90%. As regard erectile dysfunction, 5 patients reported erectile dysfunction (16.7%). Conclusions: Anastomotic urethroplasty of short segment bulbar strictures continues to have excellent success rates and durability, but some patients who undergo anastomotic urethroplasty experience de novo sexual dysfunction.